Non-intrusive Assessment of Photosystem II and Photosystem I in Whole Coral Tissues - Szabó, Milán; Larkum, Anthony W. D.; Suggett, David J.; Vass, Imre; Sass, László; Osmond, Barry; Zavafer, Alonso; Ralph, Peter J.; Chow, Wah S. (Frontiers in Marine Science, 2017)
Reef building corals (phylum Cnidaria) harbor endosymbiotic dinoflagellate algae (genus Symbiodinium) that generate photosynthetic products to fuel their host's metabolism. Non-invasive techniques such as chlorophyll (Chl) fluorescence analyses of Photosystem II (PSII) have been widely used to estimate the photosynthetic performance of Symbiodinium in hospite. However, since the spatial origin of PSII chlorophyll fluorescence in coral tissues is uncertain, such signals give limited information on depth-integrated photosynthetic performance of the whole tissue. In contrast, detection of absorbance changes in the near infrared (NIR) region integrates signals from deeper tissue layers due to weak absorption and multiple scattering of NIR light. While extensively utilized in higher plants, NIR bio-optical techniques are seldom applied to corals. We have developed a non-intrusive measurement method to examine photochemistry of intact corals, based on redox kinetics of the primary electron donor in Photosystem I (P700) and chlorophyll fluorescence kinetics (Fast-Repetition Rate fluorometry, FRRf). Since the redox state of P700 depends on the operation of both PSI and PSII, important information can be obtained on the PSII-PSI intersystem electron transfer kinetics. Under moderate, sub-lethal heat stress treatments (33°C for ~20 min), the coral Pavona decussata exhibited down-regulation of PSII electron transfer kinetics, indicated by slower rates of electron transport from QA to plastoquinone (PQ) pool, and smaller relative size of oxidized PQ with concomitant decrease of a specifically-defined P700 kinetics area, which represents the active pool of PSII. The maximum quantum efficiency of PSII (Fv/Fm) and functional absorption cross-section of PSII (σPSII) remained unchanged. Based on the coordinated response of P700 parameters and PSII-PSI electron transport properties, we propose that simple P700 kinetics parameters as employed here serve as indicators of the integrity of PSII-PSI electron transfer dynamics in corals.